Faits d’actualité - Dalpé, Jean (Assurances)

(untitled) (HEC Montréal, 1981)
Amongst the principal events dealt with in this short review of the situation is the current practice of tenders in insurance operations and their results, the technical and financial results of the insurance operations in Canada during the first six months of 1980, the frequency of automobile accidents in the province of Quebec, the financial stability in reinsurance and its conditions, Artisans and Coopérants joining together. And finally the automobile appraisal centers in Quebec.